EDGE: The sensitivity of ultra-faint dwarfs to a metallicity-dependent initial mass function. Issue 2 (21st April 2022) - Prgomet, Mateo; Rey, Martin P; Andersson, Eric P; Segovia Otero, Alvaro; Agertz, Oscar; Renaud, Florent; Pontzen, Andrew; Read, Justin I
ABSTRACT: Motivated by the observed bottom-light initial mass function (IMF) in faint dwarfs, we study how a metallicity-dependent IMF affects the feedback budget and observables of an ultra-faint dwarf galaxy. We model the evolution of a low-mass ($≈ 8 \, × \, 10^{8} \, \rm M_{\odot }$ ) dark matter halo with cosmological, zoomed hydrodynamical simulations capable of resolving individual supernovae explosions, which we complement with an empirically motivated subgrid prescription for systematic IMF variations. In this framework, at the low gas metallicities typical of faint dwarfs, the IMF of newborn stellar populations becomes top-heavy, increasing the efficiency of supernova and photoionization feedback in regulating star formation. This results in a 100-fold reduction of the final stellar mass of the dwarf compared to a canonical IMF, at fixed dynamical mass. The increase in the feedback budget is none the less met by increased metal production from more numerous massive stars, leading to nearly constant iron content at z = 0. A metallicity-dependent IMF therefore provides a mechanism to produce low-mass ($\rm M_{\star }\sim 10^3 \rm M_{\odot }$ ), yet enriched ($\rm [Fe/H]≈ -2$ ) field dwarf galaxies, thus opening a self-consistent avenue to populate the plateau in $\rm [Fe/H]$ at the faintest end of the mass–metallicity relation.